Effect of ecological factors on manifestation of respiratory diseases - O.S. Kozhyna (Zaslavsky O.Yu., 2018)
For the first time in Ukraine, phase IV of the International Study of Asthma and Allergies in Childhood (ISAAC) program was realized in Kharkiv region in 2015-2017. 6,330 questionnaires were distributed. 6,146 (97 %) schoolchildren took part in the program. 12.8 % of them had respiratory complaints: 13.2 % of children aged 6 to 7 years, 12.4 % - 13 to 14 years old. These results were compared with the data from ISAAC phase I (V.A. Ognev, 1998) to determine the dynamics of respiratory symptoms prevalence: over the last 19 years, the prevalence of respiratory symptoms has decreased by 1.6 times in children of primary school age and by 2 times - in adolescence. The study was conducted in 8 districts of Kharkiv region (Lozivskyi, Kupianskyi, Vovchanskyi, Bohodukhivskyi, Sakhnovshchynskyi, Barvinkivskyi, Derhachivskyi, Novovodolazkyi) which differ by environmental characteristics. In ecologically contaminated areas, the prevalence of wheezing is 1.4 times higher, exercise-induced asthma symptoms - 1.9 times higher and severe dyspnea attacks disturbing night sleep occur 3.4 times more often. The study is intended to improve the bronchial asthma prevention in children population of Kharkiv region.